Study on the Effects of Electrode and Microchannel Sizes on the Performance of MBEB - Basheer, Esmail Abdullah Mohammed; Abdulbari, Hayder A. (Informatics Publishing Limited, 2017)
Background/Objectives: The design and fabrication of Microfluidics-based electrochemical biosensor with high quality and the optimal effective surface area are of primary importance for more accurate result. The effects of the microelectrode size with variation in the microchannel size was investigated. Methods/Statistical Analysis: The effect of the microchannel size on the performance of the sensor was then investigated using cyclic voltammetry testing for different sizes of the fabricated channels (100, 400, 700 and 1000 μm) at electrode size of 100μm and 200μm. Findings: The electrokinetic properties of the microchannel were found to be affected by the size of both the microchannel and the electrode. The highest sensitivity of the sensor was reported at microchannel size of 700 and electrode size of 200μm. Application/Improvements: High accuracy and fast responding electrochemical biosensor are expected to be produced through the optimization of the microchannel size and the electrode surface area.